Precision neuromodulation: Promises and challenges of spinal stimulation for multi-modal rehabilitation - Bandres, Maria F.; Gomes, Jefferson L.; Moreno Romero, Gerson N.; Twyman, Avery R.; McPherson, Jacob Graves (Frontiers in Rehabilitation Sciences, 2023)
Spinal cord injury results in multiple, simultaneous sensorimotor deficits. These include, but are not limited to, full or partial paralysis of muscles below the lesion, muscle spasms, spasticity, and neuropathic pain. Bowel, bladder, and sexual dysfunction are also prevalent. Yet, the majority of emerging spinal stimulation-based therapies focus on a single issue: locomotor rehabilitation. Despite the enormous potential of these translational advances to transform the lives of people living with spinal cord injury, meaningful recovery in other domains deemed critical priorities remains lacking. Here, we highlight the importance of considering the diverse patterns of neural transmission that underlie clinically similar presentations when developing spinal stimulation-based therapies. We also motivate advancement of multi-modal rehabilitation paradigms, which leverage the dense interconnectivity of sensorimotor spinal networks and the unique ability of electrical stimulation to modulate these networks to facilitate and guide simultaneous rehabilitation across domains.